Psychosocial impact of the COVID-19 pandemic on doctors’ children: are we heading towards a mental health pandemic? - Riffat Omer; Humayun Iqbal Khan; Muhammad Khalid Masood; Najaf Masood; Fatima Tahira (Paediatrica Indonesiana, 2021)
Background The coronavirus pandemic (COVID-19) may affect the behavior of children. Non infected children of doctors seem to be susceptible to psychosocial health disorders. Objective To assess the psychosocial impact of the COVID-19 pandemic on children of doctors. Methods This questionnaire-based survey filled up by doctors was done with the Pediatric Symptom Check List-17 (PSC-17) to assess the psychosocial impact of the COVID-19 pandemic on doctors’ children aged 10-15 years with no clinical evidence of being infected with coronavirus and possible contributing factors to mental distress/psychosocial health disorders. A PSC -17 Score of >=15 was considered as a significant indicator of suspected psychosocial impact. Results Children’s mean age was 12.5 (SD 1.9) years, and 53.8% of them were male. Of 357 questionnaire responses, 36.1% had a significant PSC-17 score (>15) and a small, but significant inverse correlation was observed with age (r=-0.147; P=0.005). More screen time than usual was perceived by doctors to be the most common potential contributing factor (63%) to their children’s psychosocial impact. Conclusion The COVID-19 pandemic is likely to leave lasting effects on children’s mental health. Parents should closely monitor children for any changes in psychosocial behavior, so that timely intervention can be considered. Psychosocial screening of children is needed and should be conducted at schools.